Long-term profiling of aerosol light extinction, particle mass, cloud condensation nuclei, and ice-nucleating particle concentration over Dushanbe, Tajikistan, in Central Asia - Hofer, Julian; Ansmann, Albert; Althausen, Dietrich; Engelmann, Ronny; Baars, Holger; Abdullaev, Sabur F.; Makhmudov, Abduvosit N. (Katlenburg-Lindau : EGU, 2020)
For the first time, continuous, vertically resolved long-term aerosol measurements were conducted with a state-of-the-art multiwavelength lidar over a Central Asian site. Such observations are urgently required in efforts to predict future climate and environmental conditions and to support spaceborne remote sensing (ground truth activities). The lidar observations were performed in the framework of the Central Asian Dust Experiment (CADEX) at Dushanbe, Tajikistan, from March 2015 to August 2016. An AERONET (AErosol RObotic NETwork) sun photometer was operated at the lidar field site. During the 18-month campaign, mixtures of continental aerosol pollution and mineral dust were frequently detected from ground to cirrus height level. Regional sources of dust and pollution as well as long-range transport of mineral dust mainly from Middle Eastern and the Saharan deserts determine the aerosol conditions over Tajikistan. In this study, we summarize our findings and present seasonally resolved statistics regarding aerosol layering (main aerosol layer depth, lofted layer occurrence); optical properties (aerosol and dust optical thicknesses at 500–532 nm, vertically resolved light-extinction coefficient at 532 nm); profiles of dust and non-dust mass concentrations and dust fraction; and profiles of particle parameters relevant for liquid water, mixed-phase cloud, and cirrus formation such as cloud condensation nuclei (CCN) and ice-nucleating particle (INP) concentrations. The main aerosol layer over Dushanbe typically reaches 4–5 km height in spring to autumn. Frequently lofted dust-containing aerosol layers were observed at heights from 5 to 10 km, indicating a sensitive potential of dust to influence cloud ice formation. Typical dust mass fractions were of the order of 60 %–80 %. A considerable fraction is thus anthropogenic pollution and biomass burning smoke. The highest aerosol pollution levels (in the relatively shallow winter boundary layer) occur during the winter months. The seasonal mean 500 nm AOT (aerosol optical thickness) ranges from 0.15 in winter to 0.36 in summer during the CADEX period (March 2015 to August 2016); DOTs (dust optical thicknesses) were usually below 0.2; seasonally mean particle extinction coefficients were of the order of 100–500 Mm−1 in the main aerosol layer during the summer half year and about 100–150 Mm−1 in winter but were mainly caused by anthropogenic haze. Accordingly, the highest dust mass concentrations occurred in the summer season (200–600 µg m−3) and the lowest during the winter months (20–50 µg m−3) in the main aerosol layer. In winter, the aerosol pollution mass concentrations were 20–50 µg m−3, while during the summer half year (spring to autumn), the mass concentration caused by urban haze and biomass burning smoke decreases to 10–20 µg m−3 in the lower troposphere. The CCN concentration levels are always controlled by aerosol pollution. The INP concentrations were found to be high enough in the middle and upper troposphere to significantly influence ice formation in mixed-phase and ice clouds during spring and summer seasons.